Frequency of C4d Positivity in Membranous and other Glomerulonephritis in Renal Biopsy Specimens in a Tertiary Care Hospital - Shafique, Maria; Bukhari, Uzma; Kumar, Suresh; Raza, Muhammad; Bukhari, Asma (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the frequency of C4d positivity in Membranous and other Glomerulonephritis in renal biopsy specimens. Methodology: This cross-sectional study was carried out in the Pathology Department, Ziauddin Medical University and Hospital, Karachi, from December 2018 to April 2019. Non-probability consecutive sampling technique was used.. A sample size of 91 patients was calculated and selected by open EPI software with a 95% confidence interval. All patients of either gender with a clinical history of Glomerulonephritis were included. The diagnosis was made on sections stained with hematoxylin and eosin (H&E) along with special stains. Immunohistochemistry was performed on selected biopsies with glomerular basement thickness using the peroxidase-anti peroxidase technique for C4d. Patient data were compiled and analyzed through a statistical package for the Social Sciences (SPSS) Version 20.0. P-value ?0.05 was considered significant. Results: A total of 91 cases of the renal biopsy were evaluated. There were 51.6% (47/91) were male, and 48.4% (44/91) were female patients. There were 49 (53.8%) cases reported as Focal segmental glomerulosclerosis, 35(38.5%) were diagnosed as Membranous Glomerulonephritis, and 07 (7.7%) cases were reported as Mesangiocapillary Glomerulonephritis. The frequency distribution of C4d staining results in Membranous Glomerulonephritis was 100% (35/91), Mesangiocapillary glomerulonephritis 100% (7/91), and Focal segmental glomerulosclerosis was 0% (0/91). Conclusion: C4d positivity on immunohistochemistry (IHC) can be an important marker for diagnosing membranous nephropathy. Key Words: Glomerulonephritis, Immunofluorescence, immunohistochemistry C4d Positivity.